INVENTORY PLANNING MANAGEMENT OF LOW PRESSURE FILTER WEB (LPFW) ON KT1-BEE AIRCRAFT BASED ON RELIABILITY COMPONENT IN SKATEK 043 - Rahmawati, Fajar Khanif (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2019)
Low pressure filter web (LPFW) is one of the components on KT1-Bee aircraft that has been damaged 18 times during March 2016 to April 2017. The LPFW damage that occurred must be anticipated by planning the inventory of components, so when the same damage happens, it can be replaced immediately. Life limit of LPFW by manufacturer is 375FH. However, from the calculation with the weibull method it showed the Mean Time Between Failure (MTBF) only reaches 347,248FH. MTBF values that are smaller than the life limit component require early inventory planning. Through the Poisson method with a confidence level of 70%, the value of x = 5 is obtained. Then if the value is calculated in the recommendation based on the passion distribution with x-1, it will reach 4. From these results, the recommendation of the number of LPFW spare parts that must be prepared to avoid unserviceable aircraft is 4ea.